Molecular Self‐Assembly Regulated Dopant‐Free Hole Transport Materials for Efficient and Stable n‐i‐p Perovskite Solar Cells and Scalable Modules. (20th September 2022) - Cheng, Qinrong; Chen, Haiyang; Yang, Fu; Chen, Ziyuan; Chen, Weijie; Yang, Heyi; Shen, Yunxiu; Ou, Xue‐Mei; Wu, Yeyong; Li, Yaowen; Li, Yongfang
Abstract: Dopant‐free organic hole transport materials (HTMs) remain highly desirable for stable and efficient n ‐ i ‐ p perovskite solar cells (pero‐SCs) but rarely succeed. Here, we propose a molecular assembly strategy to overcome the limited optoelectronic properties of organic HTMs by precisely designing a linear organic small molecule BDT‐DPA‐F from the atomic to the molecular levels. BDT‐DPA‐F can assemble into a fibril network, showing an obviously improved hole mobility and decreased energy disorder. The resultant pero‐SCs showed a promising efficiency of 23.12 % (certified 22.48 %), which is the highest certified value of pero‐SCs with dopant‐free HTMs, to date. These devices also showed a weak‐dependence of efficiency on size, enabling a state‐of‐the‐art efficiency of 22.50 % for 1‐cm 2 device and 20.17 % for 15.64‐cm 2 module. For the first time, the pero‐SCs based on dopant‐free HTMs realized ultralong stabilities with T 80 lifetimes over 1200 h under operation or thermal aging at 85 °C. Abstract : A hole transport material (BDT‐DPA‐F) is designed, and it can assemble into a fibril network, showing an obviously improved hole mobility, a decreased energy disorder and high scalability. The perovskite solar cells based on BDT‐DPA‐F without any dopant obtain promising power conversion efficiencies of 23.12 % (certified 22.48 %) for small‐area devices (0.062 cm 2 ) and 20.17 % for large‐area modules (15.64 cm 2 ).